Muslim Women-Led Agriculture: Strengthen Families and Climate for SDGs in East Java, Indonesia - Arodha, Dianidza; Maya Panorama; Moh. Syawaludin; Bahrina Almas; Imamul Arifin; Hilmy Baihaqy Yussof (Profetika: Jurnal Studi Islam, 2025)
Objective: This study analyzes the contribution of Muslim women-led agriculture in Bondowoso Regency to the reduction of household carbon emissions as well as the strengthening of ecological and economic resilience based on tengka values, supporting local SDGs targets. This study also formulates a synergy model for households, Islamic boarding schools, and village governments as a form of women's empowerment aligned with global SDGs objectives. Theoretical framework: This research is based on the integration of sustainable agriculture, women's empowerment, and Islamic ecology based on local wisdom. Tengka values serve as a framework for cultural empowerment that connects low-carbon practices with women's social agency. Literature review: Literature review shows that studies on low-carbon agriculture, women's leadership, and the role of local values are still rarely integrated simultaneously. This research fills this gap through an integrated cultural and institutional approach. Methods: This study uses a qualitative approach with a case study design in Karanganyar Village, East Java. Data was obtained through interviews, observations, and document analysis. Results: The results showed that the production of local bhug-bhug feed from kitchen waste resulted in lower carbon emissions than industrial feed. This practice is able to reduce feed costs by up to 80% and strengthen household economic resilience. Implications: These findings confirm that climate change mitigation can be achieved through gender-equitable and culturally sensitive household farming practices. The synergy model of households–pesantren–village governments has the potential to become a reference for low-carbon village policies. Novelty: The novelty of this research lies in the formulation of a tengka-based women's empowerment model that integrates low-carbon agricultural practices and local institutional synergy. This study places local wisdom and religious institutions as the foundation of sustainable ecological transformation (sdgs).